Efforts to Improve Plant Reboization in Pucangrejo Village, Kendal District - Arinta Berlianti; Muhammad Faqih; Muhammad Zakarya Cakampai; Syifa Mardhiyah; Hilmi Mardinda Putri; Muhammad Habib Al Hadi; Moch. Maola Nasty Gansehawa (Universitas Palangka Raya, 2024)
Reforestation is reforestation so that nature becomes green and is usually carried out in forests that have become deforested so that they can function as they should. Not only that, there are still many benefits from this reforestation activity. Knowing the many benefits of reforestation activities, the KKN MIT 18 Posko 71 UIN Walisongo group conducted research regarding increasing reforestation in Pucangrejo village. This research used a descriptive qualitative research method for students and students to describe the environmental conditions observed in a specific, transparent and in-depth manner. The location of this research field has determined the scope of the research object.